2018
DOI: 10.1108/ijoem-01-2017-0013
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of corporate profitability: an investigation of Indian manufacturing firms

Abstract: Purpose The purpose of this paper is to examine the firm-specific and macroeconomic determinants of profitability of Indian manufacturing firms. It assesses the main determinants of firm’s profitability in the pre-crisis and post-crisis period from 2000 to 2015. Design/methodology/approach This methodology splits the factors that influence firm profitability in two groups: firm-specific (internal) factors and macroeconomic indicators. It further aims to look at the consistency of the factors in the pre-crisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
109
3
17

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(147 citation statements)
references
References 62 publications
18
109
3
17
Order By: Relevance
“…In Table 1, Nanda and Panda (2018) investigate the determinants factor of performance (ROA and NPM). On the other hand, Ndlovu and Alagidede (2018) use ROE to measure performance.…”
Section: Gaps Analysismentioning
confidence: 99%
“…In Table 1, Nanda and Panda (2018) investigate the determinants factor of performance (ROA and NPM). On the other hand, Ndlovu and Alagidede (2018) use ROE to measure performance.…”
Section: Gaps Analysismentioning
confidence: 99%
“…It is able to identify critical aspects endangering fi rm´s future and, on the other hand, it also may reveal strengths which can, when maintained and boosted, help a company become more sustainable and competitive (Hiadlovský et al, 2016). Hereby, to take right decisions, managers need to analyse their fi nancial situation, especially in respect to fi rm´s profi tability and the factors infl uencing it (Emery et al, 2007;Atrill, 2006;Hanousek et al, 2015;Zalai et al, 2016;Park & Youngtae, 2017;Beyer & Hinke, 2018). As profi t maximisation is generally one of the most signifi cant fi nancial objectives, managers try to take decisions supporting its achievement.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The investigation of factors that may have an impact on the fi rm´s profi tability can be very helpful. Their identifi cation has been one of the concerns of researchers, however, previous studies have shown inconsistent fi ndings (Alarussi & Alhaderi, 2018;Nanda & Panda, 2018). There is rather large number of studies investigating key factors determining profi tability in the banking sector.…”
Section: ľUbica Lesáková Andrea Ondrušová Miroslava Vinczeovámentioning
confidence: 99%
“…Internal factors (age, size, share, capital, liquidity) and their contribution to profitability were studied by Samiloglu and Demirgunes [21] and Asimakopoulos et al [22]. Nanda and Panda [23] confirmed firm-specific determinants as dominant players in the generation of corporate profitability and positively identified the size of a firm and its liquidity as crucial factors, while leverage was considered as a variable with a negative influence (except for during a crisis period). Schiefer and Hartmann [24], and Inci and Lee [25] observed industry-related factors.…”
Section: Literature Review and Theoretical Considerationsmentioning
confidence: 99%